2016
DOI: 10.1101/058917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A robust role for motor cortex

Abstract: The role of motor cortex in non-primate mammals remains unclear. More than a 10 century of stimulation, anatomical and electrophysiological studies has implicated neural activity in 11 this region with all kinds of movement. However, following the removal of motor cortex, rats retain 12 most of their adaptive behaviours, including previously learned skilled movements. Here we revisit 13 these two conflicting views of motor cortex and present a new behaviour assay, challenging 14 animals to respond to unexpe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 118 publications
(63 reference statements)
1
17
1
Order By: Relevance
“…This variation in motor cortical influence suggests that the specificity of behavioral deficits following lesions or pharmacological inactivation that eliminate motor cortical output does not merely reflect an inability of other motor areas to compensate during a subset of movements. Moreover, the agreement between the latencies of silencing effects during precision pull and of stimulation responses implies a direct influence of motor cortical output on muscle activity in rodents, contrary to recent claims (Lopes et al, 2016). …”
Section: Discussioncontrasting
confidence: 90%
“…This variation in motor cortical influence suggests that the specificity of behavioral deficits following lesions or pharmacological inactivation that eliminate motor cortical output does not merely reflect an inability of other motor areas to compensate during a subset of movements. Moreover, the agreement between the latencies of silencing effects during precision pull and of stimulation responses implies a direct influence of motor cortical output on muscle activity in rodents, contrary to recent claims (Lopes et al, 2016). …”
Section: Discussioncontrasting
confidence: 90%
“…Cortical control of movement may therefore have co-evolved with an increasing reliance of species on cortical processing of sensory input providing the necessary information to guide movement with accuracy and precision, especially when the extraction of sensory information requires complex processing. In agreement with such a model, effects of motor cortex lesion in rodents are most pronounced when the task requires fine digit control ( Whishaw et al., 1998 ), when animals encounter novel sensory conditions and movement coordination requires rapid sensory feedback control ( Lopes et al., 2016 ), or when animals are still in the process of learning to control the movement ( Kawai et al., 2015 ). It is thus conceivable that motor cortex functions to structure and adjust movements based on incoming sensory information processed in cortex.…”
Section: Discussionmentioning
confidence: 63%
“…Mouse visual cortex, for example, is thought to not only process visual information, but also act as a detector of visual feedback that deviates from the visual feedback based on motor output ( Attinger et al., 2017 , Fiser et al., 2016 , Zmarz and Keller, 2016 ). Consistent with the hypothesis that motor cortex might be involved in the processing of deviations of expected from actual sensory input, selective responses triggered by unexpected feedback perturbations during locomotion are present in cat motor cortex ( Marple-Horvat et al., 1993 ), and in rodents it has been shown that motor cortex is necessary for the rapid initiation of a behavioral response to an unexpected feedback perturbation ( Lopes et al., 2016 ). Moreover, exposing animals to increased demands for movement accuracy results in increased activity in motor cortex, which could be the consequence of increased precision in sensory feedback guided control of movement ( Beloozerova et al., 2010 , Beloozerova and Sirota, 1993b , Farrell et al., 2015 ).…”
Section: Introductionmentioning
confidence: 64%
“…Our results suggest that the utility of this BG pathway can be extended to generate novel task-specific motor sequences -a process that may require a motor cortex-dependent reprogramming of subcortical motor circuits. This would allow cortex to off-load the 'task' of generating specialized and stereotyped learned behaviors to subcortical circuits, making them more automatized and less prone to cortical 'interference' 126 . Consistent with this idea are observations that task-related cortical activity decreases over the course of training and with increasing automaticity 27,[127][128][129][130][131][132][133] .…”
Section: Evolutionary Considerationsmentioning
confidence: 99%